How do you find f'(x) using the definition of a derivative for #f(x)=1/sqrt(x)#?

Answer 1

The crucial step uses #(sqrtx - sqrt(x+h))(sqrtx + sqrt(x+h)) = -h#. If that's not enough of a hint, see below.

#f(x) = 1/sqrtx#
#f'(x) = lim_(hrarr0)(f(x+h)-f(x))/h#
# = lim_(hrarr0)(1/sqrt(x+h)-1/sqrtx)/h#
# = lim_(hrarr0)((sqrtx-sqrt(x+h))/(sqrt(x+h)sqrtx))/(h/1)#
# = lim_(hrarr0)((sqrtx-sqrt(x+h)))/((hsqrt(x+h)sqrtx)) #
# = lim_(hrarr0)((sqrtx-sqrt(x+h)))/((hsqrt(x+h)sqrtx)) * ((sqrtx+sqrt(x+h)))/((sqrtx+sqrt(x+h)))#
# = lim_(hrarr0)(x-(x+h))/((hsqrt(x+h)sqrtx)(sqrtx+sqrt(x+h)))#
# = lim_(hrarr0)(-h)/(hsqrt(x+h)sqrtx(sqrtx+sqrt(x+h)))#
# = lim_(hrarr0)(-1)/(sqrt(x+h)sqrtx(sqrtx+sqrt(x+h)))#
# = (-1)/(sqrtxsqrtx(sqrtx+sqrtx))#
# = (-1)/(2xsqrtx)#
Or, if you prefer #(-1)/(2x^(3/2))#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find ( f'(x) ) using the definition of a derivative for ( f(x) = \frac{1}{\sqrt{x}} ), follow these steps:

  1. Start with the definition of the derivative: [ f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} ]

  2. Substitute the function ( f(x) = \frac{1}{\sqrt{x}} ) into the formula: [ f'(x) = \lim_{h \to 0} \frac{\frac{1}{\sqrt{x + h}} - \frac{1}{\sqrt{x}}}{h} ]

  3. Rationalize the numerator: [ f'(x) = \lim_{h \to 0} \frac{\sqrt{x} - \sqrt{x + h}}{h \sqrt{x} \sqrt{x + h}} ]

  4. Combine the fractions in the numerator: [ f'(x) = \lim_{h \to 0} \frac{\sqrt{x} - \sqrt{x + h}}{h} \times \frac{1}{\sqrt{x} \sqrt{x + h}} ]

  5. Multiply and divide by the conjugate of the numerator: [ f'(x) = \lim_{h \to 0} \frac{\sqrt{x} - \sqrt{x + h}}{h} \times \frac{\sqrt{x} + \sqrt{x + h}}{\sqrt{x} + \sqrt{x + h}} ]

  6. Simplify the numerator: [ f'(x) = \lim_{h \to 0} \frac{x - (x + h)}{h(\sqrt{x} + \sqrt{x + h})} ]

  7. Cancel out ( x ) terms in the numerator: [ f'(x) = \lim_{h \to 0} \frac{-h}{h(\sqrt{x} + \sqrt{x + h})} ]

  8. Cancel out ( h ) terms in the numerator and denominator: [ f'(x) = \lim_{h \to 0} \frac{-1}{\sqrt{x} + \sqrt{x + h}} ]

  9. Substitute ( h = 0 ) into the expression: [ f'(x) = \frac{-1}{2\sqrt{x} \cdot 1} ]

  10. Simplify the expression: [ \boxed{f'(x) = -\frac{1}{2x\sqrt{x}}} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7